Plant Identification and Significance in Funeral Traditions Exemplified by Pillow Filling from a Child Crypt Burial in Byszewo (18th/19th centuries) - Jarosińska, Marta; Nowak, Sebastian; Noryśkiewicz, Agnieszka M.; Badura, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Plants have always played an important role in funeral customs. To understand their true meaning, close cooperation between the archaeologist and the archaeobotanist is needed, not only during the final interpretation, but from the very beginning, at the stage of collecting materials. In the article, plants’ identification, using both pollen and macroremains analysis, was described, based on one of the children’s burial from the Holy Trinity Church in Byszewo (18th/19th centuries). The filling of the coffin pillow consisted of numerous hop (Humulus lupulus) macroremains, the representation of which was very low in pollen sample. This is due to the fact that only female specimens of hop were inserted into the coffin. To determine the reason for using hops in funeral practices in Byszewo, ethnobotanical data was used. The following research indicates the need for the cooperation between two methods of plant identification. It will allow misinterpretations of botanical findings to be avoided.
Authors are indebted to Dr hab. Małgorzata Grupa prof UMK for reading the manuscript, her help and valuable suggestions. This work has been supported by the University of Gdańsk – research task no. 530-L145- D581-19 and the Nicolaus Copernicus University – research tasks Nos 499 and 502.
Keywords: archaeobotany; funeral plants; crypts; child burial; Byszewo; Northern Poland